Baseline adiponectin and leptin levels in predicting an increased risk of disease activity in rheumatoid arthritis: A meta-analysis and systematic review. (16th November 2016) - Cao, Heng; Lin, Jin; Chen, Weiqian; Xu, Guanhua; Sun, Chuanyin
Abstract: To determine the pathogenic role of adipokines, such as adiponectin and leptin, in rheumatoid arthritis (RA) by investigating whether serum levels of these adipokines correlated with disease activity in RA patients. Medline, Cochrane, EMBASE and Google Scholar were searched for studies published until 5 November 2015 reporting serum levels of leptin and adiponectin and measures of disease activity including DAS scores and radiographic progression scores (such as total change in SHS scores and number of erosions). Secondary outcomes included pain scores, functional status and health questionnaires. Only randomized controlled trials, cohort studies, or two-armed prospective or retrospective studies were included. A χ 2 -based test of homogeneity was performed using Cochran's Q statistic and I 2 . A total of 917 predominantly female participants (average age range, 39–56 years) from six prospective cohort studies were included for assessment. A fixed-effects analysis was applied for leptin levels due to lack of heterogeneity among the studies ( Q  = 4.4364; I 2  =   32.38). A random-effects analysis was applied to serum levels of adiponectin because of significant heterogeneity between studies ( Q  = 4.444, I 2  =   77.50%). Serum leptin levels were higher in RA patients with high disease activity (pooled SMD: 0.53, 95% CI: 0.24–0.82); however, serum adiponectin levels did not correlate with RA disease activity (pooled OR: 1.38, 95% CI: 0.77–2.47). The meta-analysis provides an additional factor to determine high disease activity index in RA, that is, serum leptin levels, which can be of benefit when choosing treatment strategies.